Sebuah latihan ketahanan mengurangi stres oksidatif pada orang dewasa muda dengan kelebihan berat badan - Setiakarnawijaya, Yasep; Taufik, Muhamad Syamsul; Widiastuti, Widiastuti; Kuswahyudi, Kuswahyudi; Purwoto, Septyaningrum Putri (Universitas Nusantara PGRI Kediri, 2023)
This study aims to prove the effects of a single bout of endurance exercise on decreased oxidative stress in young adults with overweight. This study used the true experimental method with a pretest-posttest control group design. Twenty overweight women between the ages of 20 and 23 were recruited from college students and randomly divided into CON (n = 10, control group without exercise) and EEx (n = 10, endurance exercise group). The endurance exercise intervention is carried out once by running on a treadmill with an intensity of 60-70% HRmax for 40 minutes/exercise sessions. Malondialdehyde (MDA) levels as a biomarker of oxidative stress were measured 30 minutes pre-exercise and 24 hours post-exercise using the Thiobarbituric Acid Reactive Substance (TBARs) method. The results showed that MDA levels significantly decreased in the endurance training group compared to the control group. Results of analysis of MDA levels between pre-exercise and post-exercise in CON (819.00±66.47 vs. 853.00±113.55 ng/mL; (P > 0.05), EEx (810.00±120.19 vs. 596.00±67.57 ng/mL; (P < 0.05). Based on the results of this study, it was concluded that a single session of endurance exercise at an intensity of 60-70% HRmax for 40 minutes reduces oxidative stress in overweight adolescent females.